A brief mindfulness-based stress reduction intervention for nurses and nurse aides - Mackenzie, Corey S.; Poulin, Patricia A.; Seidman-Carlson, Rhonda (Applied nursing research, 2006)
Whereas the causes and negative consequences of stress among nurses are well known, less is known about effective ways to reduce or prevent this growing problem. Mindfulness-based stress reduction programs are proving to be effective in reducing stress and improving health in a variety of clinical populations. A smaller body of evidence suggests that these programs are also effective for nonclinical populations at risk for stress-related health problems. This study involved the development and evaluation of a brief 4-week mindfulness intervention for one such group—nurses and nurse aides. In comparison with 14 wait-list control participants, 16 participants in the mindfulness intervention experienced significant improvements in burnout symptoms, relaxation, and life satisfaction. The results of this pilot study, together with a natural fit between mindfulness philosophy and nursing practice theory, suggest that mindfulness training is a promising method for helping those in the nursing profession manage stress, even when provided in a brief format.